Epidemiology and zoonotic transmission of mcr-positive and carbapenemase-producing Enterobacterales on German turkey farms - Nordhoff, Katja; Scharlach, Martina; Effelsberg, Natalie; Knorr, Carolin; Rocker, Dagmar; Claussen, Katja; Egelkamp, Richard; Mellmann, Alexander C.; Moss, Andreas; Müller, Ilona; Roth, Sarah Andrea; Werckenthin, Christiane; et al. (Frontiers in Microbiology, 2023)
The emergence of carbapenem-resistant bacteria causing serious infections may lead to more frequent use of previously abandoned antibiotics like colistin. However, mobile colistin resistance genes (mcr) can jeopardise its effectiveness in both human and veterinary medicine. In Germany, turkeys have been identified as the food-producing animal most likely to harbour mcr-positive colistin-resistant Enterobacterales (mcr-Col-E). Therefore, the aim of the present study was to assess the prevalence of both mcr-Col-E and carbapenemase-producing Enterobacterales (CPE) in German turkey herds and humans in contact with these herds. In 2018 and 2019, 175 environmental (boot swabs of turkey faeces) and 46 human stool samples were analysed using a combination of enrichment-based culture, PCR, core genome multilocus sequence typing (cgMLST) and plasmid typing. mcr-Col-E were detected in 123 of the 175 turkey farms in this study (70.3%). mcr-Col-E isolates were Escherichia coli (98.4%) and Klebsiella spp. (1.6%). Herds that had been treated with colistin were more likely to harbour mcr-Col-E, with 82.2% compared to 66.2% in untreated herds (p = 0.0298). Prevalence also depended on husbandry, with 7.1% mcr-Col-E in organic farms compared to 74.5% in conventional ones (p < 0.001). In addition, four of the 46 (8.7%) human participants were colonised with mcr-Col-E. mcr-Col-E isolates from stables had minimum inhibitory concentrations (MICs) from 4 to ≥ 32 mg/L, human isolates ranged from 4 to 8 mg/L. cgMLST showed no clonal transmission of isolates. For one farm, plasmid typing revealed great similarities between plasmids from an environmental and a human sample. No CPE were found in turkey herds or humans. These findings confirm that mcr-Col-E-prevalence is high in turkey farms, but no evidence of direct zoonotic transmission of clonal mcr-Col-E strains was found. However, the results indicate that plasmids may be transmitted between E. coli isolates from animals and humans.